Pengaruh Risiko Bisnis, Ukuran Perusahaan, Pertumbuhan Aset dan Pertumbuhan Penjualan Terhadap Struktur Modal Perusahaan Cosmetics Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Kamelia rizqi Indridiani; R. Gatot Heru Pranjoto (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study was to determine the effect of the Influence of Business Risk, Company Size, Asset Growth and Sales Growth partially and simultaneously on the Capital Structure of Cosmetics companies listed on the Indonesia Stock Exchange for the period 2017 -2021. This research was conducted in a quantitative descriptive manner using secondary data obtained at the Indonesia Stock Exchange. The population of this study namely as many as 7 Cosmetics companies listed on the Indonesia Stock Exchange. The sampling method obtained as many as 7 companies that match certain criteria. For testing using the T Test (partial) and F Test (simultaneous). The results of the T test show that Business Risk, Firm Size, Asset Growth and Sales Growth partially have no significant effect on Capital Structure. While the results of the F test show that business risk, company size, asset growth and sales growth simultaneously have no significant effect on capital structure.